Study of Some Factors Affecting the Stability of R.C. Buildings Subjected to Progressive Collapse Loads (Comparative Study: ACI Method versus GSA and UFC Methods) - Mohammed Al-Shaier; Fakery Khalil; Mohammed Al-Sharief (African Journal of Advanced Pure and Applied Sciences, 2026)
Progressive collapse of reinforced concrete buildings is defined as a phenomenon initiated by the local failure of one or more structural members, which may propagate and result in the partial or total collapse of the structure. This type of failure is usually caused by loads that are not considered in the original design and are therefore classified as abnormal loads. Due to its importance in achieving safer structural systems, this study examines progressive collapse analysis using the Alternate Load Path (AP) method and the Tie Force (TF) method, both of which are widely applied within linear static analysis frameworks. The analyses are carried out using the advanced structural analysis software SAP2000. The ALP method is based on four damage scenarios that assume the removal of a single ground-floor column located at the corner, edge, or interior of the building. The demand-to-capacity ratios of beams adjacent to the removed column are evaluated to assess the likelihood of progressive collapse. When these ratios exceed the limits specified by design codes, additional steel reinforcement is provided to the affected beams to reduce the ratios to acceptable levels and enhance structural robustness. The TF method focuses on strengthening the building by providing various types of structural ties to improve continuity and resistance against progressive collapse. In this study, a generalized design curve was developed and divided into three design regions. When the ratio , the GSA design approach is adopted, whereas for , the ACI-based approach is recommended. The effects of column displacement in both directions and the influence of span length on building stability under progressive collapse loading were also investigated.